Prospective Clinical Utility Study of the Use of the 21-Gene Assay in Adjuvant Clinical Decision Making in Women With Estrogen Receptor-Positive Early Invasive Breast Cancer: Results From the SWITCH Study - Gligorov, Joseph (Oncologist, 2015)
BACKGROUND. The 21-gene Oncotype DX Recurrence Score assay is a validated assay to help decide the appropriate treatment for estrogen receptor-positive (ER+), early-stage breast cancer (EBC) in the adjuvant setting. The choice of adjuvant treatments might vary considerably in different countries according to various treatment guidelines. This prospective multicenter study is the first to assess the impact of the Oncotype DX assay in the French clinical setting. METHODS. A total of 100 patients with ER+, human epidermal growth factor receptor 2-negative EBC, and node-negative (pN0) disease or micrometastases in up to 3 lymph nodes (pN1mi) were enrolled. Treatment recommendations, physicians’ confidence before and after knowing the Recurrence Score value, and physicians’ perception of the assay were recorded. RESULTS. Of the 100 patients, 95 were evaluable (83 pN0, 12 pN1mi). Treatment recommendations changed in 37% of patients, predominantly from chemoendocrine to endocrine treatment alone. The proportion of patients recommended chemotherapy decreased from 52% pretest to 25% post-test. Of patients originally recommended chemotherapy, 61% were recommended endocrine treatment alone after receiving the Recurrence Score result. For both pN0 and pN1mi patients, post-test recommendations appeared to follow the Recurrence Score result for low and high values. Physicians’ confidence improved significantly. CONCLUSION. These are the first prospective data on the impact of the Oncotype DX assay on adjuvant treatment decisions in France. Using the assay was associated with a significant change in treatment decisions and an overall reduction in chemotherapy use. These data are consistent with those presented from European and non-European studies. IMPLICATIONS FOR PRACTICE: This study shows that in estrogen receptor-positive, human epidermal growth factor receptor 2-negative early breast cancer (either node-negative or with micrometastases in up to 3 lymph nodes), Oncotype DX testing is associated with a treatment recommendation change in more than a third of patients (primarily from chemoendocrine treatment to endocrine treatment alone but also in the opposite direction) and an overall reduction in chemotherapy use. These results are consistent with those from other decision impact studies worldwide and further emphasize the role of Oncotype DX testing in management of early breast cancer, as reflected in international treatment guidelines.